Partial trisomy for short and long arm of chromosome no. 5: Two cases of two possible syndromes. - Zabel, B (1978)
We report 2 patients from different families with malformation-retardation syndromes caused by a partial trisomy of the long and of the short arm of chromosome 5, respectively (case 1: 46,XX,der(3),t(3;5)(p27;p13)mat; case 2: 46,XY,der(22),t(5;22)(q33;q13)pat). Several members of these families were balanced translocation carriers. Our cases are compared with those cited in the literature. The possibility of delineating a 5p- and a 5q-partial-trisomy syndrome is discussed.